The Role of Venture Investments in Financing Innovative Activities and the Digital Sector - Qarajanova Gulnoza Tolliyevna (International Journal on Economics, Finance and Sustainable Development, 2022)
Venture financing, which is a multi-faceted financing of research results in the field of science, is of particular importance in the concentration of financial resources and their orientation to priority areas of innovation by creating a rational system for financing innovation activities. This article analyzes the theoretical aspects and a number of advantages of venture financing of innovative processes.